Hiding audio file in video frames using wavelet technique - Raja, R. Vinston; Senthamilarasi, N.; Christal Mary, S. Suma; Umashankar, J. S. (International Journal of Engineering and Technology, 2018)
Steganography derives covering private or enigma sound inside a transporter in impalpable way. In this paper we are wearing out avideo steganography calculation in context of Haar Integer Wavelet Transforms (IWT) and extraction in luminance and chrominance (YCbCr) bits of the video records. In this approach, the cover-video is disconnected into YCbCr charts and the sound perfectly healthy is implanted into the IWT coefficients. The presented sound is expelled from stego-video utilizing the switch method of information disguising. Haar wavelet change is related with get the low rehash sub-band in a photograph to cover information. The rehash sub-packs are (LL, LH, HL and HH).The work of different scientists is talked about video steganography and their strategies for embeddings and extraction of information. With the advance of progression and mixed media data, Videos and electronic pictures is expanding rapidly. A tremendous measure of data can be secured in video documents. It contains number of edges played over some dubious time apportioning. .Data can be secured in any or number of edges. Also, Attacker or Human eye can't see the closeness of message in video since video plot is unmistakable for a little measure of time.